Integrating disaster risk reduction and climate change adaptation: a systematic literature review. (15th March 2020) - Islam, Shafiqul; Chu, Cordia; Smart, James C. R.; Liew, Leong
ABSTRACT: Climate Change is widely acknowledged to be increasing the scale and intensity of disasters. Literatures stress the need to link Disaster Risk Reduction (DRR) and Climate Change Adaptation (CCA) to make more efficient use of resources and avoid overlapping. Despite growing recognition of the necessity for such linkages, little study has yet investigated the challenges confronting integration and how best to overcome them. We conducted a systematic literature review to better articulate the rationale for integrating DRR and CCA, to identify acknowledged challenges to integration, and to provide directions for future research. The review followed PRISMA guidelines and examined 37 peer-reviewed studies on linking DRR and CCA. Key challenges in integration are found to be: lack of capacity among actors and institutions, policy gaps, mismatches, governance failure, lack of coordination, fund-shortages, and obstructive influence from the influential decision makers. These challenges are underpinned by the political economy— the nexus of influencing actors, and their interests in funding mechanisms surrounding DRR and CCA. Given the underrepresentation of political economy analysis in the literature, this study recommends the needs for an in-depth political economy analysis to determine efficient governance frameworks, improved policies, and mechanisms for effective integration of DRR and CCA in different contexts.